Analisis Implementasi Skrining ISPA Digital di RSUD Cipayung - Ekonugroho Prasetyo (Yayasan Pendidikan Medika Indonesia, 2022)
At the beginning of 2020, the COVID-19 outbreak spread rapidly in various countries around the world. The spread of the COVID-19 outbreak is very fast and concerning. Symptoms of COVID-19 are very unclear, clinical manifestations can range from asymptomatic to severe symptoms and even death. The hospital in an effort to provide safe and quality services conducts a screening and triage process for all visitors to prevent infection transmission in the hospital area. In carrying out the screening, it creates queues and takes time so that it can lead to the potential for transmission. RSUD Cipayung is trying to change the screening process from manual to digital application in order to accelerate the process. The purpose of this study was to determine the effectiveness of the implementation of digital ARI screening in Cipayung Hospital. This research is a descriptive research with a cross sectional approach. The sample was taken with the number of respondents as many as 52 outpatient visitors consisting of visitors who had experienced digital screening and manual screening with consecutive sampling techniques. Research shows that the use of digital ARI screening applications provides faster service times. Queue waiting times are faster than ever. The process of implementing digital screening is better than manual screening. Most of the respondents are very satisfied with this application and have an efficiency impact on the use of ATK and hospital human resources. Hospitals can improve these applications and increase visitor objectivity in filling out digital applications by increasing supervision by health workers.